Brief Report: Lopinavir Hair Concentrations Are the Strongest Predictor of Viremia in HIV-Infected Asian Children and Adolescents on Second-Line Antiretroviral Therapy. (1st December 2017) - Pintye, Jillian; Bacchetti, Peter; Teeraananchai, Sirinya; Kerr, Stephen; Prasitsuebsai, Wasana; Singtoroj, Thida; Kuncze, Karen; Louie, Alexander; Koss, Catherine A.; Jin, Chengshi; Phung, Nhi; Horng, Howard; et al.
Abstract : Background: Children/adolescents display suboptimal antiretroviral therapy (ART) adherence and outcomes versus adults. Hair ART concentrations are objective adherence measures that predict viremia in adults but longitudinal data on hair levels in pediatric populations is limited. We assessed the predictive utility of hair lopinavir (LPV) levels on viremia among youth on second-line ART. Methods: We examined predictors of viremia (HIV-1 RNA >400 and >1000 copies/mL) at least 24 weeks after switch to LPV-based second-line ART in a cohort of HIV-infected Asian children followed between 2011 and 2014. Small hair samples, HIV-1 RNA, and self-reported adherence were collected biannually. Hair concentrations of LPV were measured through liquid chromatography/tandem mass spectrometry using validated methods. Time-to-first viremia was examined using discrete-time Cox models. Results: Overall, 244 children met the inclusion criteria for the present analysis. Approximately half (55%) were boys and the median age 10 years [interquartile range (IQR) 7–13]; 40% were older than 11 years. At switch to second-line ART, median CD4 count was 300 (IQR 146–547) cells/mm 3 and median HIV-RNA level was 5.0 (IQR 4.3–5.6) log10 /mL. Median time of study follow-up was 48 weeks and a median of 3 (range 1–5) hair samples were collected from each participant. Adjusting for age, sex, country, self-reported adherence, CD4, and HIV-RNA, higher LPV hair concentrations were the strongest predictor of lower odds of viremia (HIV-RNA >400 copies/mL adjusted odds ratio = 0.41 per doubling in hair concentration, 95% confidence interval: 0.29 to 0.58, P < 0.001; HIV-RNA >1000 copies/mL, adjusted odds ratio = 0.54, 95% confidence interval: 0.45 to 0.65, P < 0.001). Conclusions: Hair concentrations predict viremia among children with HIV on second-line ART and could guide clinical decisions for this population.